Urgensi Penerapan Etika Profesi Terhadap Upaya Penegakan Hukum di Indonesia - Salmanita Shalsabella Pramudita; Kayus Kayowuan Lewoleba (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Ethics is an assessment of whether someone's behavior or actions are right or wrong. Meanwhile, morality is the rightness or wrongness of human behavior. Ethics are ideas and ideals about the motives for moral action or behavior. As the author, I took the title: